Incidence and Timing of Thrombosis After the Norwood Procedure in the Single‐Ventricle Reconstruction Trial - Michael H. White; Michael Kelleman; Robert F. Sidonio; Lazaros Kochilas; Kavita N. Patel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Thrombosis is common in infants undergoing staged surgeries for single‐ventricle congenital heart disease. The reported incidence and timing of thrombosis varies widely, making it difficult to understand the burden of thrombosis and develop approaches for prevention. We aimed to determine the timing and cumulative incidence of thrombosis following the stage I Norwood procedure and identify clinical characteristics associated with thrombosis. Methods and Results We analyzed data from the Pediatric Heart Network Single Ventricle Reconstruction trial from 2005 to 2009 and identified infants with first‐time thrombotic events. In 549 infants, the cumulative incidence of thrombosis was 21.2% (n=57) from stage I through stage II. Most events occurred during stage I (n=35/57, 65%), with a median time to thrombosis of 15 days. We used a Cox proportional hazards model to estimate the association of clinical variables with thrombosis. After adjusting for baseline variables, boys had a higher hazard of thrombosis (adjusted hazard ratio [HR], 2.69; 95% CI, 1.44–5.05; P=0.002), non–hypoplastic left heart syndrome cardiac anatomy was associated with a higher early hazard of thrombosis (adjusted HR, 3.93; 95% CI, 1.89–8.17; P<0.001), and longer cardiopulmonary bypass time was also associated with thrombosis (per 10‐minute increase, adjusted HR, 1.07; 95% CI, 1.01–1.12; P=0.02). Lower oxygen saturation after the Norwood procedure increased the hazard for thrombosis in the unadjusted model (HR, 1.08; 95% CI, 1.02–1.14; P=0.011). Conclusions Thrombosis affects 1 in 5 infants through Stage II discharge, with most events occurring during stage I. Male sex, non–hypoplastic left heart syndrome anatomy, longer cardiopulmonary bypass time, and lower stage I oxygen saturation were associated with thrombosis.